2022
DOI: 10.1177/08465371221127236
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pectus Excavatum With Ventricular Remodelling and Mitral Valve Abnormalities in Marfan Syndrome

Abstract: Background: Marfan syndrome (MFS) is an inherited connective tissue disorder. Pectus excavatum (PEX) is common in MFS. The purpose was to evaluate the association of PEX with cardiovascular manifestations of MFS, biventricular size and function. Methods: MFS adults undergoing cardiac MRI were retrospectively evaluated. Exclusion criteria were incomplete cardiac MRI, significant artifacts, co-existent ischaemic or congenital heart disease. Haller Index (HI) ≥3.25 classified patients as PEX positive (PEX+) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…1). Twenty-five studies 22,24,34–56 totaling 2800 patients (mean age 27.9 ± 13.9 years, 48.2% females) affected by the most common TSA (PE, PC, scoliosis, SBS, and MS) were thus included in this systematic review. A summary of the included studies’ characteristics is reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1). Twenty-five studies 22,24,34–56 totaling 2800 patients (mean age 27.9 ± 13.9 years, 48.2% females) affected by the most common TSA (PE, PC, scoliosis, SBS, and MS) were thus included in this systematic review. A summary of the included studies’ characteristics is reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%